2002
DOI: 10.1590/s1517-74912002000100006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of intracanal medicaments on strict anaerobes by means of the broth dilution method

Abstract: The determination of bacterial susceptibility to intracanal medicaments is a necessity. Nevertheless, few studies utilize the proper methodology to carry out that evaluation with anaerobes. In this study, the steps of a broth dilution method, carried out in microplates (microdilution) and tubes (macrodilution), to test the effect of traditional intracanal medicaments on anaerobic bacteria are described. The results are presented as values of minimal inhibitory and bactericidal concentrations (MIC and MBC). Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(13 reference statements)
0
6
0
2
Order By: Relevance
“…Working inoculums were prepared by transferring 200 μL aliquots of this suspension to three test tubes and adjusting the volumes to 10 mL with reinforced clostridial medium (RCM; Oxoid) to give final concentrations of 2.0 × 10 5 CFU mL –1 . 12 …”
Section: Methodsmentioning
confidence: 99%
“…Working inoculums were prepared by transferring 200 μL aliquots of this suspension to three test tubes and adjusting the volumes to 10 mL with reinforced clostridial medium (RCM; Oxoid) to give final concentrations of 2.0 × 10 5 CFU mL –1 . 12 …”
Section: Methodsmentioning
confidence: 99%
“…Ohara et al evaluated the antibacterial effect of several irrigants and found that Ca(OH) 2 was totally ineffective as saline 39. Studies that compared the effect of various agents showed that Ca(OH) 2 had only a weak effect 40,41,42,43. More recent studies that compared Ca(OH) 2 with other agents reported that Ca(OH) 2 was less effective than others 44,45,46.…”
Section: Reviewmentioning
confidence: 99%
“…It was observed that although oleum pedum did not have any antibacterial property, the use of calcium hydroxide in high concentrations such as those present in OCHS acted as growth-inhibitory. Calcium hydroxide is used widely in endodontic treatment and in vitro evidence demonstrates it suppresses the growth of Candida albicans [28] and certain other anaerobically growing bacteria [29] although limited antimicrobial efficacy has translated in vivo following the analysis of root canals post-treatment [30,31]. In our in vitro assays, in contrast to calcium hydroxide, OCHS did not have any antibacterial effect which may suggest a counteracting effect of the other components of OCHS to calcium hydroxide.…”
Section: Discussionmentioning
confidence: 99%